CHANGING THE MINDSET OF THE YOUNG GENERATION INTO GREAT ENTREPRENEURS IN THE GLOBAL ERA ( Training Entrepreneurship For Students and Teachers at GENOVA Pasir Vocational School White – Nagawutung – Lembata – NTT) - Christiyanti Abel; Thomas Ola Langoday (PT. Jurnal Center Indonesia Publisher, 2025)
Becoming a great entrepreneur in the global era is not as easy as flipping the palm of your hand. A successful and happy great entrepreneur is not solely determined by high academic performance, a high IQ, or attending a prestigious school. In fact, GPA, IQ, and attending a top school do not even rank among the top ten factors that guarantee someone will become a great and successful entrepreneur. What truly determines entrepreneurial greatness and success are soft skills. The top 10 soft skills referred to are: Honesty (Being honest with all people) ranked first, followed by Strong Discipline (Being well-disciplined); Sociability (Getting along with people); Support from a Partner (Having a supportive spouse); Hard Work (Working harder than most people); Passion for the Work (Loving my career/business); Leadership (Having strong leadership qualities); Competitive Personality (Having a very competitive spirit/personality); Well-Organized Life (Being very well-organized); and finally, Ability to Sell Ideas (Having an ability to sell my ideas/products). These ten soft skills will become even more meaningful when accompanied by a good heart, positive thinking, wise words, good deeds, good habits, positive culture, and strong character—all of which shape good fortune. Ultimately, good fortune begins with a good heart.